THE MODERATING ROLE OF RELIGIOUS INVOLVEMENT IN THE RELATIONSHIP OF SPIRITUALITY AND RELIGIOSITY WITH INTEGRITY AMONG REGIONAL GOVERNMENT INSPECTORATE AUDITORS IN INDONESIA - FITRI, DINIYAH AULIA; SIDDIQ, DEDI MUHAMMAD (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study discusses the role of spirituality and religiosity in predicting integrity moderated by the religious involvement of local government auditors. Design/methodology/approach: Data collection was conducted by distributing paper-based questionnaires to 122 local government auditor respondents in two regions in West Java, Indonesia. Findings: This study found that spirituality and religiosity have a positive and significant relationship with auditor integrity. Research limitations/implications: Inspectorate in two regions in West Java, Indonesia. Practical implications: Spirituality and religiosity will increasingly influence the integrity of auditors when accompanied by the auditor's religious involvement. Originality/value: Religiosity and spirituality have a significant influence on auditor integrity. However, religious involvement only moderates the relationship between religiosity and integrity, not spirituality and integrity. Paper type: Research paper